Instrumento de rastreio para disfagia orofaríngea no Acidente Vascular Encefálico - Parte I: evidências de validade baseadas no conteúdo e nos processos de resposta - Almeida, Tatiana Magalhães de; Cola, Paula Cristina; Pernambuco, Leandro de Araújo; Magalhães, Hipólito Virgílio; Magnoni, Carlos Daniel; Silva, Roberta Gonçalves da (FapUNIFESP (SciELO), 2017)
Purpose: The aim of the present study was to identify the evidence of validity based on the content and response process of the Rastreamento de Disfagia Orofaríngea no Acidente Vascular Encefálico (RADAVE; Screening Tool for Oropharyngeal Dysphagia in Stroke). Methods: The criteria used to elaborate the questions were based on a literature review. A group of judges consisting of 19 different health professionals evaluated the relevance and representativeness of the questions, and the results were analyzed using the Content Validity Index. In order to evidence validity based on the response processes, 23 health professionals administered the screening tool and analyzed the questions using a structured scale and cognitive interview. Results: The RADAVE structured to be applied in two stages. The first version consisted of 18 questions in stage I and 11 questions in stage II. Eight questions in stage I and four in stage II did not reach the minimum Content Validity Index, requiring reformulation by the authors. The cognitive interview demonstrated some misconceptions. New adjustments were made and the final version was produced with 12 questions in stage I and six questions in stage II. Conclusion: It was possible to develop a screening tool for dysphagia in stroke with adequate evidence of validity based on content and response processes. Both validity evidences obtained so far allowed to adjust the screening tool in relation to its construct. The next studies will analyze the other evidences of validity and the measures of accuracy.
Screening tool for oropharyngeal dysphagia in stroke - Part I: evidence of validity based on the content and response processes